Pengaruh Kepemimpinan Transformasional Dan Kompetensi Terhadap Kinerja Karyawan - Dyah Agustin Widhi Yanti; Mursidi Mursidi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Running a business requires accuracy and speed from the operational process to the process of delivering goods to consumers. This development is supported by the ease of delivery of goods, both from producers to consumers. Goods can be shipped by land, sea, and air shipping. This is a business opportunity for business people who have a strategic location for the delivery route. This study uses a quantitative approach, by collecting data through surveys. Transformational leadership has a significant effect on the performance of employees of PT. Surabaya Container Terminal. Transformational Leadership of PT. The strong Surabaya Container Terminal will have an impact on employee performance. This is due to the application of idealized influence, the behavior of a leader that makes his followers admire, respect, and trust him. Competency results have a significant effect on the performance of employees of PT. Surabaya Container Terminal. This means that competence can improve employee performance.